Answer:
The new equation is y = 1/3 cos(x) - 2 ⇒ 3rd answer
Explanation:
* Lets revise the trigonometry transformation
- If the equation is y = a cos(x - c) + d
# a is the scale factor of a vertical stretch or compression
# c is the phase shift (negative is to the right, positive is to the left)
# d is the vertical shift
- If y = cos(x)
∴ a = 1 , c = 0 , d = 0
* Now lets solve the problem
∵ There is a vertical compression by a factor of 1/3
∴ a = 1/3
∵ There is a translation 2 units down (vertical translation)
∴ d = -2
∵ There is now phase shift (horizontal translation)
∴ c = 0
* Now lets write the new equation
∴ y = 1/3 cos(x) - 2
* For more understand look to the attached color graph
- The red is y = cos(x)
- The blue is y = 1/3 cos(x) - 2